Androsace halleri subsp. nuria Schönsw. & Schneew. (Primulaceae), a new taxon from the eastern Pyrenees (Spain, France) - Schönswetter, Peter; Magauer, Marianne; Schneeweiss, Gerald M. (Phytotaxa, 2015)
In the course of molecular phylogeographical investigations in the Aretia group of Androsace (Primulaceae), a previously unrecognised entity from the eastern Pyrenees (Spain/France) was identified as genetically distinct lineage. The entity is here morphologically characterised and described as new subspecies, Androsace halleri subsp. nuria Schönsw. & Schneew.